2015
DOI: 10.1016/j.jconrel.2015.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Kinome-level screening identifies inhibition of polo-like kinase-1 (PLK1) as a target for enhancing non-viral transgene expression

Abstract: Human cells contain hundreds of kinase enzymes that regulate several cellular processes, which likely include transgene delivery and expression. We identified several kinases that influence gene delivery and/or expression by performing a kinome-level screen in which, we identified small-molecule kinase inhibitors that significantly enhanced non-viral (polymer-mediated) transgene (luciferase) expression in cancer cells. The strongest enhancement was observed with several small-molecule inhibitors of Polo-like K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Interestingly, it has also been shown that inhibition of JAK/STAT signaling with the JAK inhibitor AG-490 significantly increases luciferase expression in PC3 cells. 42 Altogether, these results show that plasmid DNA activates an innate immune response that increases IL-6 expression and hinders transgene expression, but inhibition of different parts of this pathway can restore transgene expression.…”
Section: Effects Of Inhibitors On Inflammatory Cytokine (Il-6) Expresmentioning
confidence: 81%
“…Interestingly, it has also been shown that inhibition of JAK/STAT signaling with the JAK inhibitor AG-490 significantly increases luciferase expression in PC3 cells. 42 Altogether, these results show that plasmid DNA activates an innate immune response that increases IL-6 expression and hinders transgene expression, but inhibition of different parts of this pathway can restore transgene expression.…”
Section: Effects Of Inhibitors On Inflammatory Cytokine (Il-6) Expresmentioning
confidence: 81%
“…In addition to vehicles and promoters, the effects of several other variables were also tested to optimize transfection efficiency in Jurkat T cells. For example, cells were treated with small molecule inhibitors that have previously been shown to enhance transgene expression in other cell types (e.g., BX795, MS‐275, AG‐490, and HMN‐214) (Christensen et al, 2015; Sutlu et al, 2012). One of the inhibitors (iCRT14) enhanced luciferase expression approximately threefold, but did not significantly enhance transfection efficiency (i.e., %EGFP + cells, shown in Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the following agents should act to address the biology of ARMS by acting at genomic and proteomic levels: 1) Entinostat by virtue of its ability to: a) inhibit class I HDAC [32] and thereby, to interrupt the YY1-EZH2-HDAC1 inhibition of miR-29b2 and mir-29c allowing arrest of ARMS cell proliferation and promoting differentiation [1117, 28]; and b) its ability to effect direct transcriptional supression of PAX3:FOXO1 [33] and to inhibit the phosphorylative activation of PAX3—FOXO1 by polo-like kinase (PLK)1 [29, 34, 35]; 2) celecoxib inhibits the NF-kappaB pathway at multiple points [36] and should reduce the overproduction of YY1; 3) sulforaphane, a nutraceutical suppresses polycomb group protein level including EZH2 [37] and this should promote alveolar rhabdomyosarcoma's differentiation to a more benign form, induce apoptosis in the tumor cells [38] and reduce the survival of alveolar rhabdomyosarcoma leading to elimination of the tumor (in the latter study, sulforaphane was also shown to decrease the mRNA and protein levels of PAX3-FKHR, MYCN and MET in ARMS cells); 4) retinoic acid upregulates miR-214 which downregulates EZH2 protein in embryonic stem cells and miR-214-mediated EZH2 protein reduction accelerates skeletal muscle cell differentiation [39] (Both all-trans retinoic acid, ATRA and 9-cis retinoic acid suppressed the cell growth of alveolar rhabdomyosarcoma with evidence of a differentiating effect [40]. ATRA increased the expression of some genes associated with muscle differentiation and slowed the proliferation and promoted a more differentiated myogenic phenotype in ARMS cell lines [41].…”
Section: Discussionmentioning
confidence: 99%